Effects of Cytokinins and Auxins on Direct and Indirect Regeneration of Banana (Musa Acuminata L.) Cv. Berangan - Tuavao, Siosi Lolohea (2004)
The ultimate challenge to banana industry in Malaysia is the constant threat from disease infection such as Fusarium wilt (race 4) and Sigatoka leaf spot. Conventional breeding of banana remains difficult due to high sterility and polyploidy level, therefore biotechnological techniques must be integrated into banana improvement programmes. The present study was divided into two parts and directed to cater for the abovementioned scenario. Therefore, a direct and indirect regeneration protocol is needed for in-vitro propagation and genetic manipulation, respectively. To study the effect of cytokinins and auxins on shoot and root proliferation, excised shoot-tip with rhizome and leaf base (1.0 cm2 base x 1.5 cm) was cultured on modified Murashige and Skoog (1962) nutrient medium. The modified solid medium was supplemented with various concentrations (0.5, 2.0, 4.0, 8.0, 16.0 mg/L) of cytokinins (BAP, Kinetin, Adenine hemisulphate) for shoot proliferation and (0.10, 0.25, 0.50, 1.00, 1.50, 2.00, 2.50 mg/L) auxins (NAA, IBA, IAA) for rooting study. The results demonstrated that shoot and root proliferation were significantly dependent on type and concentration of cytokinins and auxins. The optimum cytokinin concentration for shoot proliferation was 8.0 mg/L BAP with 8.4 shoots per explant in the 5th subculture. Four mg/L BAP is recommended for in-vitro shoot proliferation, as 8.0 mg/L BAP had no significant different from the effect on shoot induction. The maximum number of roots, 10.5 and 9.0 per explant was achieved at 2.00 mg/L IBA and 2.00 mg/L IAA, respectively on 30th day of inoculation. Therefore, treatment with either 2.00 mg/L IBA or 2.00 mg/L IAA can be used for in-vitro rooting of banana cv. Berangan. Both recommended cytokinin and auxin levels are subjected to in-vitro screening and field evaluation to avoid the onset of somaclonal variants. In the second study, rhizome (1.0 x 1.0 x 0.5 cm) was cultured on solid MS media supplemented with various levels (0.5, 2.0, 4.0, 8.0, 16.0 mg/L) of auxins (NAA, PCPA, 2-4,D) to determine their effects on callus induction. PCPA and 2-4,D treatments failed to induce callus. Treatment with 4.0 mg/L NAA produced 5% callus, whereas treatments with 8.0 and 16.0 mg/L both produced 10% callus per replication. Subculturing did not promote callus induction. The follow-up experimental results showed that 12 mg/L NAA induced the maximum percentage of callus (93%) per replication after 2 months culture. However, the results of follow-up experiment must be further evaluated for the type, intensity and regenerability of callus.